2013
DOI: 10.4238/2013.august.20.2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of Hsp60 and HSF-1 in primary rat myocardial cells in vitro under heat stress

Abstract: ABSTRACT. The mechanisms involved in sudden animal death due to acute heart failure during heat stress are not well understood. We examined the relationship between heat stress-induced variations of protective Hsp60 and expression of its regulatory factor, HSF-1, in heat-stressed primary myocardial cells of neonatal rats in vitro through cardiac enzyme detection, immunoblotting, immunocytochemistry, and qPCR. Increases in cardiac damage-related enzyme levels demonstrated injury to myocardial cells after heat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Moreover, HSF1 may play different roles in its interaction with HSPs in different species or cell types. STRING analysis confirmed our previous finding that HSF1 is not the sole factor for HSP60 ( 36 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, HSF1 may play different roles in its interaction with HSPs in different species or cell types. STRING analysis confirmed our previous finding that HSF1 is not the sole factor for HSP60 ( 36 ).…”
Section: Discussionsupporting
confidence: 86%
“…It has been suggested that HSP70 represses HSF1 during heat stress ( 12 ). Furthermore, a previous study indicated that HSF1 is not the sole factor for HSP60 in rats [Buriro et al ( 36 )]. Furthermore, data analysis confirmed that the expression levels of CRYAB were inconsistent with those of HSF1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart and liver diseases or damage are always accompanied by elevated blood levels of AST [ 36 ]. In vitro tests showed that the LDH content is a sensitive parameter of myocardial damage [ 6 ]. In the present study, heart damage was monitored in real-time during HS based on fluctuations in AST, CK and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on HSPs mainly focused on the regulation of function and expression, including transcription and translation levels (Buriro et al ; Morimoto ). The concentration of mRNA template was regulated for optimal sample amplification.…”
Section: Discussionmentioning
confidence: 99%